An Update on Corneal Biomechanics and Architecture in Diabetes. (2nd June 2019) - del Buey, María A.; Casas, Paula; Caramello, Constanza; López, Nuria; de la Rica, Marisa; Subirón, Ana B.; Lanchares, Elena; Huerva, Valentín; Grzybowski, Andrzej; Ascaso, Francisco J.
Abstract : In the last decade, we have witnessed substantial progress in our understanding of corneal biomechanics and architecture. It is well known that diabetes is a systemic metabolic disease that causes chronic progressive damage in the main organs of the human body, including the eyeball. Although the main and most widely recognized ocular effect of diabetes is on the retina, the structure of the cornea (the outermost and transparent tissue of the eye) can also be affected by the poor glycemic control characterizing diabetes. The different corneal structures (epithelium, stroma, and endothelium) are affected by specific complications of diabetes. The development of new noninvasive diagnostic technologies has provided a better understanding of corneal tissue modifications. The objective of this review is to describe the advances in the knowledge of the corneal alterations that diabetes can induce.